Synthetic antimicrobial peptide LD4-PP protects the host against E. coli-induced cell death - Mohanty, Soumitra; White, John Kerr; Yin, Yundi; Muhammad, Taj; Demirel, Isak; Strömstedt, Adam A.; Gunasekera, Sunithi; Ferraz, Natalia; Göransson, Ulf; Brauner, Annelie (Frontiers in Immunology, 2025)
With antibiotic resistance being a major global concern, there is a huge need of new treatment options to fight bacterial infections. In this study, we highlight the antibacterial and host-protective roles of a novel synthetic antimicrobial peptide in uropathogenic Escherichia coli–infected uroepithelial cells. This peptide, designed from a fragment of human cathelicidin LL-37 and named LD4-PP, was found to be highly potent against clinical isolates of E. coli as well as ESBL-producing and multi-drug resistant E. coli. Additionally, LD4-PP inhibited the formation of new biofilm, damaging both the bacterial surface and the bacterial genome. LD4-PP also modulated the host cell lipid vacuole, caveolin-1, and Rho GTPase B affecting bacterial survival. Furthermore, LD4-PP exerts immunomodulatory effects by modulating free radical formation, expression of antioxidants, and inflammasome-mediated cell death. Pronounced uroepithelial cell death was observed after E. coli infection which was significantly inhibited by LD4-PP without affecting the cellular toxicity. Overall, the peptide LD4-PP is shown to be a strong candidate for future clinical applications, particularly to prevent and treat urinary tract infections.